Hinge action versus grip in translocation by RNA polymerase. Issue 1 (1st January 2018) - Nedialkov, Yuri A.; Opron, Kristopher; Caudill, Hailey L.; Assaf, Fadi; Anderson, Amanda J.; Cukier, Robert I.; Wei, Guowei; Burton, Zachary F.
ABSTRACT: Based on molecular dynamics simulations and functional studies, a conformational mechanism is posited for forward translocation by RNA polymerase (RNAP). In a simulation of a ternary elongation complex, the clamp and downstream cleft were observed to close. Hinges within the bridge helix and trigger loop supported generation of translocation force against the RNA–DNA hybrid resulting in opening of the furthest upstream i−8 RNA–DNA bp, establishing conditions for RNAP sliding. The β flap tip helix and the most N-terminal β′ Zn finger engage the RNA, indicating a path of RNA threading out of the exit channel. Because the β flap tip connects to the RNAP active site through the β subunit double-Ψ–β-barrel and the associated sandwich barrel hybrid motif (also called the flap domain), the RNAP active site is coupled to the RNA exit channel and to the translocation of RNA–DNA. Using an exonuclease III assay to monitor translocation of RNAP elongation complexes, we show that K + and Mg 2+ and also an RNA 3′-OH or a 3′-H2 affect RNAP sliding. Because RNAP grip to template suggests a sticky translocation mechanism, and because grip is enhanced by increasing K + and Mg 2+ concentration, biochemical assays are consistent with a conformational change that drives forward translocation as observed in simulations. Mutational analysis of the bridge helix indicates that 778-GARKGL-783 ( Escherichia coli numbering) is a homeostatic hinge that undergoes multiple bends to compensate for complex conformational dynamics during phosphodiester bond formation and translocation.